Análise da rugosidade, brilho e cor de resinas compostas para dentes clareados, submetidas ao envelhecimento artificial acelerado e a ação de soluções ácidas e corantes - Barbosa, Ana Flávia Lemos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The aim of this study was to evaluate the roughness, brightness and color of composite resin to bleached teeth submitted to accelerated artificial aging and immersed in acid and coloring agents with different curing lights. The preparation of the specimens was carried out in a Teflon matrix with 5mm in diameter and 1.5mm thick, totaling 80 specimens. The samples were divided into 4 experimental groups containing 20 tablets each according to the type of resin: Opallis (GI), Renamel Microfill (GII), Filtek Z350 XT (GIII), IPS EmpressDirect (GIV). Ten tablets of each group were light cured with the curing of broad-spectrum LED VALO for 20 seconds and the other ten tablets of each group were with the curing light Ultraled for 40 seconds according to the manufacturer's recommendations. After obtaining the specimens was done polishing with silicon carbide sandpaper in descending order grain. The tablets then underwent initial analysis of surface roughness by profilometer (SJ-401) brightness by means of Glossmeter (Novo-Curve) and colored by the ultraviolet reflection spectrophotometer (UV Model -2450). Done the initial analysis procedures, test samples were subjected to an accelerated artificial aging process by an aging chamber UVB / condensation and then immersion in acid solution (Hydrochloric acid and phosphoric acid) and colorant (Red Wine) for 1 week at 37 ° C in each solution. Between immersion and other test specimens were immersed in distilled water for 24 hours. Finally, the final analysis was performed following the same procedure as the initial analysis. Regarding the color parameter of composite resins evaluated, there was no significant influence between them, and was not observed influence of curing light. The parameters of the surface roughness after the realization of the challenges despite being observed higher initial roughness...

O objetivo desse trabalho foi avaliar a rugosidade, brilho e cor de resinas compostas para dentes clareados submetidas ao envelhecimento artificial acelerado e imersas em agentes ácidos e corantes com diferentes fotopolimerizadores. A confecção dos espécimes foi realizada através de uma matriz de Teflon com 5mm de diâmetro e 1,5mm de espessura, totalizando 80 corpos de prova. Os corpos de prova foram divididos em 4 grupos experimentais contendo 20 pastilhas cada de acordo com o tipo de resina: Opallis (GI), Renamel Microfill (GII), Filtek Z350 XT (GIII), IPS EmpressDirect (GIV). Dez pastilhas de cada grupo foram fotopolimerizadas com o fotopolimerizador LED VALO de amplo espectro por 20 segundos e as outras dez pastilhas de cada grupo foram com o fotopolimerizador Ultraled por 40 segundos de acordo com as recomendações do fabricante. Após a obtenção dos corpos de prova, foi feito o polimento com lixas de carbeto de silício em ordem decrescente de granulação. As pastilhas, em seguida, foram submetidas à análise inicial da rugosidade superficial, por meio de rugosímetro (SJ-401), do brilho por meio de Glossmeter (Novo-Curve,) e da cor por meio do espectrofotômetro de reflexão ultravioleta (Modelo UV-2450). Realizados os procedimentos de análises iniciais, os corpos de provas foram submetidos à um processo de envelhecimento artificial acelerado, por meio de uma câmara de envelhecimento UVB/condensação e depois à imersão em soluções ácidas (Ácido Clorídrico e Fosfórico) e corante (Vinho Tinto) durante 1 semana a 37 °C em cada solução. Entre uma imersão e outra os corpos de prova foram mergulhados em água destilada por 24 horas. Por ultimo, foi feita a análise final seguindo o mesmo procedimento da análise incial. Em relação ao parâmetro cor das resinas compostas avaliadas, não foi...
Keywords: Resinas compostas; Aspereza de superfície; Cor; Composite resins